Association between years of competition and shoulder function in collegiate swimmers - Dischler, J. D.; Baumer, T. G.; Finkelstein, E.; Siegal, D. S.; Bey, M. J. (Sports Health: A Multidisciplinary Approach, 2018)
Background: Shoulder injuries are common among competitive swimmers, and the progression of shoulder pathology is not well understood. The objective of this study was to assess the extent to which years of competitive swim training were associated with physical properties of the supraspinatus muscle and tendon, shoulder strength, and self-reported assessments of shoulder pain and function. Hypothesis: Increasing years of competition will be associated with declining physical properties of the supraspinatus muscle/tendon and declining self-reported assessments of pain and function. Study Design: Descriptive epidemiology study. Level of Evidence: Level 4. Methods: After institutional approval, 18 collegiate female swimmers enrolled in the study. For each swimmer, supraspinatus tendon thickness was measured; tendinosis was assessed using ultrasound imaging, supraspinatus muscle shear wave velocity was assessed using shear wave elastography, isometric shoulder strength was measured using a Biodex system, and self-reported assessments of pain/function were assessed using the Western Ontario Rotator Cuff (WORC) score. All subjects were tested before the start of the collegiate swim season. Linear regression was used to assess the association between years of competition and the outcome measures. Results: Years of participation was positively associated with tendon thickness (P = 0.01) and negatively associated with shear wave velocity (P = 0.04) and WORC score (P < 0.01). Shoulder strength was not associated with years of participation (P > 0.39). Conclusion: Long-term competitive swim training is associated with declining measures of supraspinatus muscle/tendon properties and self-reported measures of pain and function. Although specific injury mechanisms are still not fully understood, these findings lend additional insight into the development of rotator cuff pathology in swimmers. Clinical Relevance: Lengthy swimming careers may lead to a chronic condition of reduced mechanical properties in the supraspinatus muscle and tendon, thereby increasing the likelihood of rotator cuff pathology.